MANAGEMENT OF COLLAR ROT OF GROUNDNUT THROUGH SEED TREATMENT: Life Science-Agricultural Science - K. B. RAKHOLIYA; K. B. JADEJA; A. M. PARAKHIA (International Journal of Life Science and Pharma Research, 2012)
Groundnut is an economic important edible oilseed crop. Groundnut suffers seed, soil and foliar diseases. Among the groundnut diseases, collar rot is one of the economic important disease. Collar rot damaged regularly due to its seeds and soil borne nature. This disease has prevalent in almost all groundnut growing states. This disease is extensive in kharif than rabi/summer season. Field experiment was conducted for two years to find out effective fungicides for control of collar rot of groundnut. Nine treatments including five fungicides along with check were laid in randomized block design with three replications. Fungicides viz. vitavax 200 wp (carboxin 37.5% + thiram 37.5%), carboxin, ipconazole, kodiak, thiram, and mancozeb were tested in field conditions. Minimum disease incidence (5.16%) and maximum pod yield (1232 kg/ha) were recorded in the treatment of vitavax 200 wp 4.0g/kgseed followed by ipconazole 3.8 FS (0.1ml) + thiram 75wp (2.5g/kgseed) and vitavax 200 wp 3.0g/kg seed.